Gambaran Perubahan Hemodinamik Pada Anestesi Regional Dengan Teknik Epidural Block Di Rumah Sakit Umum Daerah Cut Meutia Aceh Utara - Nabhani Nabhani; Andang Soedarmono; Arifindi Arifindi (Journal Pharma Saintika, 2021)
Background : Epidural anesthesia is a type of neuraxial blockade that can be used during surgery, postoperatively and in pain management with the advantage of decreasing hemodynamic status gradually so as to reduce the risk of cardiovascular effects. Objective: To describe the hemodynamic changes in regional anesthesia with the epidural block technique. Research method: quantitative descriptive with cross-sectional design. Respondents in the study were 20 people who underwent surgery with epidural anesthesia from February 2022 to April 2022. The analysis used univariate analysis. Results: the mean systolic blood pressure 20 minutes before epidural anesthesia was 134.75 mmHg and the average systolic blood pressure 20 minutes after epidural anesthesia was 110.85 mmHg The average diastolic blood pressure 20 minutes before epidural anesthesia was 81.80 mmHg and the mean Diastolic blood pressure 20 minutes after epidural anesthesia was 64.90 mmHg. The average heart rate 20 minutes before epidural anesthesia was 77.25 times per minute and the average heart rate 20 minutes after epidural anesthesia was 67.70 times per minute. The average oxygen saturation 20 minutes prior to epidural anesthesia was 97.20% and the average oxygen saturation 20 minutes after epidural anesthesia was 94.55%.